From Threat to Right: Rethinking Immigration Policy Through Competing Global Paradigms - Purnomo, Agung Sulistyo; Zulfa, Eva Achjani; Rofii, Muhammad Syaroni; Revindo, Mohamad Dian (Universitas Sultan Ageng Tirtayasa, 2025)
This article critically re-examines how immigration is framed across five dominant global paradigms: security, economic utility, humanitarian obligation, cultural integration, and global mobility. Drawing on a critical interpretive synthesis of interdisciplinary literature, it unpacks the ideological, ethical, and policy logics embedded in each framework. While each paradigm offers distinct insights, the analysis reveals their internal contradictions, blind spots, and overlapping tensions. The paper argues for a pluralistic and ethically grounded approach to migration governance, one that integrates competing logics without collapsing complexity. By mapping these paradigms and their normative stakes, the study offers a conceptual toolkit for designing migration policies that are context-sensitive, morally coherent, and institutionally realistic. It contributes to a growing body of scholarship that challenges technocratic and securitarian approaches to migration, calling instead for frameworks that are attentive to justice, human agency, and global interdependence. In a world increasingly defined by mobility, inequality, and uncertainty, this article contends that rethinking immigration governance is not only possible but necessary. Through a nuanced engagement with diverse schools of thought, it seeks to enrich scholarly debate and inform principled policymaking that reflects both empirical realities and ethical imperatives.